Simultaneous targeting of prostate stem cell antigen and prostate‐specific membrane antigen improves the killing of prostate cancer cells using a novel modular T cell‐retargeting system. Issue 13 (22nd July 2014) - Arndt, Claudia; Feldmann, Anja; Koristka, Stefanie; Cartellieri, Marc; Dimmel, Maria; Ehninger, Armin; Ehninger, Gerhard; Bachmann, Michael
<x xml:space="preserve">Abstract</x> BACKGROUND Recently, we described a novel modular platform technology in which T cell‐recruitment and tumor‐targeting domains of conventional bispecific antibodies are split to independent components, a universal effector module (EM) and replaceable monospecific/monovalent target modules (TMs) that form highly efficient T cell‐retargeting complexes. Theoretically, our unique strategy should allow us to simultaneously retarget T cells to different tumor antigens by combining the EM with two or more different monovalent/monospecific TMs or even with bivalent/bispecific TMs, thereby overcoming limitations of a monospecific treatment such as the selection of target‐negative tumor escape variants. METHODS In order to advance our recently introduced prostate stem cell antigen (PSCA)‐specific modular system for a dual‐targeting of prostate cancer cells, two additional TMs were constructed: a monovalent/monospecific TM directed against the prostate‐specific membrane antigen (PSMA) and a bivalent/bispecific TM (bsTM) with specificity for PSMA and PSCA. The functionality of the novel dual‐targeting strategies was analyzed by performing T cell activation and chromium release assays. RESULTS Similar to the PSCA‐specific modular system, the novel PSMA‐specific modular system mediates an efficient target‐dependent and ‐specific tumor cell lysis at low E:T ratios and picomolar Ab concentrations. Moreover, by combination of the EM with either the bispecific TM directed to PSMA and PSCA or both monospecifc TMs directed to either PSCA or PSMA, dual‐specific targeting complexes were formed which allowed us to kill potential escape variants expressing only one or the other target antigen. CONCLUSIONS Overall, the novel modular system represents a promising tool for multiple tumor targeting. Prostate 74: 1335–1346, 2014. © 2014 Wiley Periodicals, Inc.